Wykorzystanie nowoczesnych koncepcji i metod zarządzania do osiągania strategicznej elastyczności organizacji - Osbert-Pociecha, Grażyna (A New Approaches and Tools of Management for Gaining the Strategic Flexibility of an Organization, 2006)
In this article the problem of relation between new approaches and tools of management and strategic flexibility of a firm is taken up. It has been pointed out that these methods are used mostly to achieve operational efficiency and it is necessary to create also other approaches and tools for strategic flexibility of a firm.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 115-121